THE PECULIARITY OF THE TURKISH THEME IN I.S. SHMELEV`S PROSE - Svetlana V. Sheshunova (Alfred Nobel University Journal of Philology, 2019)
The article analyzes the specifics of understanding of Turkish culture in the works of I.S. Shmelev. On the basis of stories “Gassan and His Jaddy” (1906), “Kuzma the Soldier” (1915), “Trebizond cognac” (1938), novels “The Story of a Love” (1927), “The Nurse from Moscow” (1933), and tale “Under the Mountains” (1910) the actualization of the writer’s military, religious, family, domestic and love themes are studied. Russia was at war with Turkey more often than with any other countries. During the 18th and 19th centuries it lost no less than 740 thousand people in the Turkish wars, so it is quite natural that in its artistic consciousness there was a negative image of Turkey, which was repeatedly pointed out by researchers, emphasizing in Russian literature the perception of Turkey as an enemy and hostility of the Russian people in relation to the traditions, customs and way of life of the Turks. In the literary works by I.S. Shmelev the Turkish theme is revealed in the comprehension of the Russian man of Turkish culture. The writer’s view becomes more objective, covering both superstitious ideas of the Russian people about the Turks as a dark force, and attempts to learn a different world, to compare it with Russian reality. In this aspect, the “own” / “the other” opposition is actualized, but without the traditional hostility. Thus, in his understanding of military subjects the writer emphasizes the respect for the enemy’s military art, the absence of animosity towards each other among Russian and Turkish soldiers; touching on the religious theme, I.S. Shmelev shows Turkey through the eyes of a man of Muslim culture – a Crimean Tatar, for whom Turkey embodies the dream of a just land, where justice reigns. The study of the Turkish theme in the prose of the writer allows us to conclude that among the numerous characters of I.S. Shmelev, entering into relations with the Turks, only two episodic characters perceive them as a hostile force. In the majority of cases, in contrast to the literary tradition, relations between Russians and Turks are developing in the artistic world of Shmelev in a benevolent and sometimes even idyllic way. In stories “Kuzma the Soldier” and “Trebizond cognac” this idyllic nature of the relationship is observed even between military opponents. Misinterpretations of human behaviour in the writer’s literary works do not lead to interethnic or inter-religious conflicts, but sometimes even contribute to the success of Russian-Turkish intercultural communication. Thus, the originality of the Turkish theme in the prose of Shmelev is a clear example of overcoming the age-old perception of the neighbour as an enemy.